2015
DOI: 10.3892/mmr.2015.3258
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces inflammation and facilitates lung metastasis in a breast cancer model via the prostaglandin E2-EP2 pathway

Abstract: Inflammation is a potent promoter of tumor metastasis. The aim of the present study was to explore the function of systemic inflammation in the formation of lung metastasis of breast cancer cells in a mouse model. BALB/c mice were injected intraperitoneally with lipopolysaccharide (LPS) in order to establish an inflammatory animal model and 4T1 murine breast cancer cells were injected through the tail vein to induce lung metastasis. The levels of proinflammatory cytokines were evaluated by ELISA. Metastases on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 40 publications
(43 reference statements)
1
43
0
Order By: Relevance
“…A series of studies of prostaglandin in cancers showed that the subtype of EPs effect in different cancers was variable [5, 6, 31]. A recent study showed that PGE2 induces lung metastasis in breast cancers via EP2 [32]. However, in endometrial cancers, no result of PGE2 functional activation has ever been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies of prostaglandin in cancers showed that the subtype of EPs effect in different cancers was variable [5, 6, 31]. A recent study showed that PGE2 induces lung metastasis in breast cancers via EP2 [32]. However, in endometrial cancers, no result of PGE2 functional activation has ever been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In such a model of continuous LPS stimulation, EndMT might be involved not only in pulmonary fibrosis but also in pathological angiogenesis as is observed in tumor progression (54). Indeed, LPS were reported to induce lung metastasis of breast cancer (31). Thus how EndMT changes according to dose or duration of LPS or with other changes to the mouse model will be an issue to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Eicosanoids can also indirectly affect cancer growth. For example, PGE 2 induces aromatase expression, which is relevant to survival from postmenopausal breast cancer (39), in addition to the more direct effects of PGE 2 on driving breast cancer growth and metastases (33, 40, 41). Eicosanoids can be measured in tissues, but in epidemiological studies stable metabolites have more often been measured in urine.…”
Section: Pro-inflammatory Pathways Associated With Obesity Increase Rmentioning
confidence: 99%